TAFE accounting : to trial balance - Mroczkowski, Nicholas A.; Yates, Lindsay; Fleay, Daryl (Melbourne, VIC : Nelson, 1995)
This book is about: Accounting-concepts and environment; Business documents and journal; Ledger accounts and the trial balance; Bank reconciliation; ...
Keywords: Accounting; Bookkeeping; Accounting; Bookkeeping